Modified Vaccinia Ankara–Vectored Vaccine Expressing Nucleoprotein and Matrix Protein 1 (M1) Activates Mucosal M1-Specific T-Cell Immunity and Tissue-Resident Memory T Cells in Human Nasopharynx-Associated Lymphoid Tissue. (19th November 2019) - Puksuriwong, Suttida; Ahmed, Muhammad S; Sharma, Ravi; Krishnan, Madhan; Leong, Sam; Lambe, Teresa; McNamara, Paul S; Gilbert, Sarah C; Zhang, Qibo
Abstract: Background: Increasing evidence supports a critical role of CD8 + T-cell immunity against influenza. Activation of mucosal CD8 + T cells, particularly tissue-resident memory T (TRM ) cells recognizing conserved epitopes would mediate rapid and broad protection. Matrix protein 1 (M1) is a well-conserved internal protein. Methods: We studied the capacity of modified vaccinia Ankara (MVA)–vectored vaccine expressing nucleoprotein (NP) and M1 (MVA-NP+M1) to activate M1-specific CD8 + T-cell response, including TRM cells, in nasopharynx-associated lymphoid tissue from children and adults. Results: After MVA-NP+M1 stimulation, M1 was abundantly expressed in adenotonsillar epithelial cells and B cells. MVA-NP+M1 activated a marked interferon γ–secreting T-cell response to M1 peptides. Using tetramer staining, we showed the vaccine activated a marked increase in M158–66 peptide-specific CD8 + T cells in tonsillar mononuclear cells of HLA-matched individuals. We also demonstrated MVA-NP+M1 activated a substantial increase in TRM cells exhibiting effector memory T-cell phenotype. On recall antigen recognition, M1-specific T cells rapidly undergo cytotoxic degranulation, release granzyme B and proinflammatory cytokines, leading to target cell killing. Conclusions: MVA-NP+M1 elicits a substantial M1-specific T-cell response, including TRM cells, in nasopharynx-associated lymphoid tissue, demonstrating its strong capacity to expand memory T-cell pool exhibiting effector memory T-cell phenotype, therefore offering great potential for rapid and broad protection against influenza reinfection. Abstract : Modified vaccinia Ankara–vectored vaccine expressing nucleoprotein and matrix protein 1 (MVA-NP+M1) activates a substantial increase in anti-influenza M1-specific T cells, including fast-reacting tissue-resident memory T cells in human nasopharynx mucosal tissue. It is therefore a promising mucosal vaccine candidate.